Chromosome sensitivity to bleomycin in G2 lymphocytes from Down syndrome patients - Bartholomei-Santos, Marlise Ladvocat [UNESP]; De Lucca, Edmundo José [UNESP] (FapUNIFESP (SciELO), 1997)
Several studies have demonstrated that lymphocytes from patients with Down syndrome (DS) exhibit an increased frequency of chromosome aberrations when they are exposed to ionizing radiation or to chemicals at the G0 or G1 phases of the cell cycle, but not at G2 when compared to normal subjects. To determine the susceptibility of DS lymphocytes at G2 phase, bleomycin, a radiomimetic agent, was used to induce DNA breaks in blood cultures from 24 Down syndrome patients. All the patients with DS showed free trisomy 21 (47,XX + 21 or 47,XY + 21). Individuals that showed an average number of chromatid breaks per cell higher than 0.8 were considered sensitive to the drug. No control child showed susceptibility to bleomycin, and among the 24 patients with DS, only one was sensitive to the drug. No significant difference was observed between the two groups, regarding chromatid break frequencies in treated G2 lymphocytes. The distribution of bleomycin-induced breaks in each group of chromosomes was similar for DS and controls. No significant difference was found in the response to bleomycin between male and female subjects. Probably, the main factor involved in chromosome sensitivity of lymphocytes from patients with DS is the phase of the cell cycle in which the cell is treated.
Keywords: bleomycin; bleomycin sulfate; antibiotic sensitivity; blood culture; cell cycle g2 phase; child; chromatid; chromosome aberration; controlled study; dna strand breakage; down syndrome; female; human; human cell; infant; ionizing radiation; lymphocyte culture; male; trisomy 21